Development Of History Learning Module For High School In Palembang City - Maulana Muhammad; Hudaidah Hudaidah; Supriyanto Supriyanto (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2018)
A research of “Development of Learning Module for Senior High School at Palembang. As Problem analyisis is how to develop historical and practical learning module at Senior High School Muhammadiyah 1 Palembang. The purpose of this reasearch is to produce learning module on learning history for Senior High School Muhammadiyah 1 Palembang. This research is a kind of development research that use the model of dick and carey. The validity of this learning media is assessed by three adept consist of material, language, and instructional design. Value obtained in the validation process are material: 3.80 languages: 3.90 and lesson design: 4.00 All is in valid category by using valid product it can be seen that obtained with pretest of 25,9% and posttest of 77,0% after a field, this indicates increasing of 51,1% with a value of N-Gain 0.68% so it can be concluded that module learning media history of five days five nights war for schools at Palembang valid and practical.